The effects of long-term diet and omega-3 fatty acid supplementation on coagulation factor VII and serum phospholipids with special emphasis on the R353Q polymorphism of the FVII gene - Lindman, Anja S.; Pedersen, Jan I.; Hjerkinn, Elsa M.; Arnesen, Harald; Veierød, Marit B.; Ellingsen, Ingrid; Seljeflot, Ingebjørg (Thrombosis and Haemostasis, 2004)
The aim of the present study was to investigate the effect of long-term diet and very long chain n-3 fatty acids (VLC n-3) intervention on plasma coagulation factor VII (FVII), cholinecontaining phospholipids (PC) and triglycerides (TG), especially related to the R353Q polymorphism of the FVII gene. The present investigation included 219 subjects from the Diet and Omega-3 Intervention Trial on atherosclerosis (DOIT), a 2x2 factorial designed study in elderly men with long-standing hypercholesterolemia. The subjects were randomly allocated to receive placebo capsules (corn oil) (control), placebo capsules and dietary advice (“Mediterranean type” diet), VLC n-3 capsules, or VLC n-3 capsules and dietary advice combined. The R353Q genotype and the levels of FVIIc, FVIIag, FVIIa, PC, and TG at baseline and after 6 months were determined. Diet interention was followed by a significant reduction of 5.1% in the levels of FVIIag and 2.4 mU/ml in FVIIa (95% CI −7.4, −2.9, and −3.8, −1.1, respectively) (both p<0.001) compared to the no diet group, independent of genotype. No effects of diet intervention on FVIIc, PC or TG were observed. After VLC n-3 supplementation the TG levels were significantly reduced compared to placebo (p=0.01), whereas all FVII levels and PC remained unchanged. Dietary advice towards a “Mediterranean type” diet, but not VLC n-3 supplementation, was shown to reduce the levels of FVIIag and FVIIa after 6 months, independent of genotype. The results indicate the dietary advice to be more favourable in reducing this risk factor for CVD as compared to specific VLC n-3 supplementation.
Keywords: Coagulation factor VII; R353Q; diet; omega-3 fatty acids; phospholipids